Parallèles : Praha 96 - 97 Paris - Bruthansová, Tereza; Lemaire, Gérard-Georges; Nuridsany, Michel; Troncy, Eric; Leturcq, Armelle; Jouannais, Jean-Yves; Barbier, Didier; Horová, Andela; Prague (Prague : Edition AHA, 1996)
Daguin, Pierre ; Ohannessian, Antoinette ; Paris, Guillaume ; Ramette, Philippe ; Robert, Jean-Christophe
Prague, 8 octobre au 3 novembre 1996
kunstcatalogus